A Novel Method of End-to-Side Microvascular Anastomosis Using T-Shaped Metal Stents: A Porcine Study. Issue 4 (19th June 2022) - Sugiura, Yasushi; Sarukawa, Shunji; Kamochi, Hideaki; Takamatsu, Kensuke; Ohta, Kunihiro; Mori, Yoshiyuki; Yoshimura, Kotaro; Inoue, Keita
Abstract : Abstract: End-to-side anastomosis requires highly specialized techniques. An easy end-to-side anastomosis technique enables anastomosis of vessels with different diameters and under various situations. We invented T-shaped metal stents and evaluated novel methods of end-to-side sutureless anastomosis, confirming their safety, effectiveness, and operability. We performed 8 end-to-side sutureless anastomoses in 4 7- to 11-month-old, male Mexican hairless piglets. After induction of anesthesia, the left femoral artery was resected by approximately 8 cm, and the superior and posterior stumps of the resected femoral artery underwent an end-to-side anastomosis with the right femoral artery by the placement of the metal stents with subsequent use of adhesive for the circumferential area. The patency of blood vessels and the presence of thrombosis were evaluated by ultrasonography or contrast-enhanced computed tomography and histology 4 weeks postoperatively. All the animals survived the procedure; no thrombosis was identified in any of the 8 anastomosis sites according to imaging studies performed 4 weeks postoperatively. Histological examination confirmed the probe patency of blood vessels and neointimal cell proliferation around stent branches. End-to-side anastomosis is possible with T-shaped metal stents. In the future, we aim for the practical application of these stents by improving their operability.